Bio‐Inspired Plasmonic Photocatalysts. Issue 3 (14th December 2018) - Liu, Zhihua; Leow, Wan Ru; Chen, Xiaodong
Abstract: The conversion of solar energy to sustainable energy sources is a significant field of study for the relief of the world's energy problems, and among the various strategies developed, semiconductor photocatalysts have received significant attention as a promising candidate due to their attractive efficiency, mild reaction conditions, and low cost. The enhancement of such photocatalysts with plasmonic materials, by virtue of the Schottky junction and localized surface plasma resonance phenomenon, could facilitate the rapid progress in enhancement of photocatalytic efficiency under visible light irradiation. To further improve photocatalytic efficiency, scientists look to nature for inspiration, culminating in the evolution of complex hierarchical structures in order to fully utilize the potential of solar energy. In the past decade, there has been significant progress in the development of bio‐inspired plasmonic photocatalysts, such as antireflective surfaces, 3D photonic structures, and branched structures. This review describes the state‐of‐the‐art bio‐inspired light manipulation approaches, as well as future challenges in solar energy harvesting by plasmonic photocatalysts. Abstract : Inspired by the delicate design in biologic systems, plasmonic photocatalyst with hierarchical structure could facilitate the rapid enhancement of photocatalytic efficiency under visible light irradiation. It increases the prospect to use full spectrum of sunlight for environmental and energy related applications such as water splitting, pollutant treatment, and carbon dioxide reduction.